Meaning of fiction in formation of students` identity - Abisheva, Saule; Polyak, Dina; Seidullaeva, Gulzhan; Kermeshova, Zhanna; Sabirova, Dina (Opción, 2019)
Moral, intellectual, and esthetic development of children and teenagers are directly connected with the food for thought received by them. In this research, we will consider how basic provisions of the Convention and as a method allocate the basic institutes influencing processes of socialization of the child`s identity. One of the most important factors influencing children's reading is access to the book. In order the interest in reading did not die away, the process of reading needs to be supported. Books have to be available to the child, and the repertoire of reading must be wide and various.